PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA EDUKASI BAHAYA KEBAKARAN DAN UPAYA PENYELAMATAN DIRI DENGAN METODE PROBLEM BASED LEARNING BERBASIS HIGHER ORDER THINKING SKILLS PADA SISWA KELAS V - Putri Probowati; Wibowo, Basuki; Amiruddin, Jafar (LPPM, Universitas Negeri Jakarta, 2021)
Children's limited understanding of danger and self-protection causes children to be less able to anticipate and cope with dangerous conditions that arise around them. This can be fatal for the safety of the child. Even more so when there are no adults around the children so they cannot optimally look after and supervise the children. One way to make children safe from danger is to increase their understanding of danger and ways to overcome danger through self-safety education from an early age. This study discusses the development of learning tools in the form of syllabus, lesson plans and learning media in the form of education cards using the Problem Based Learning (PBL) method based on Higher Order Thinking Skills (HOTS). This study aims to increase students' understanding of the dangers of fire and self-rescue efforts in an emergency when a fire occurs. The population in this study was the fifth grade students at SDN Pondok Kelapa 04 totaling 30 students. This study uses the R&D method with the ADDIE model. The assessment of learning devices in this study was declared feasible from the results of the validation of the experts. This study conducted a reliability test using the KR-20 method to obtain a result of 0.82 and it was stated that this study had a very high reliability value. And test the validity using the Pearson Moment correlation technique to get results above the value of 0.3 and it is stated that this research is valid. Keywords: Learning Tools, Fire Safety, ADDIE, Problem Based Learning, Higher Order Thinking